Komunitas Belajar Sebagai Strategi Adaptasi Sumber Daya Manusia Dalam Mengelola Perubahan - Widiastuti, Eka; Junaidah, Junaidah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to formulate a comprehensive human resource (HR) adaptation strategy in response to shifts in education policy following the leadership transition from Nadiem Makarim to Abdul Mu‘ti. Employing a qualitative case study design, the research adopts a descriptive-analytical approach with HR personnel at SD Negeri 01 Rejosari as the primary subjects. Data sources include in‑depth interviews with teachers and educational staff, participant observation during learning community activities, and relevant policy and school reports. Data collection techniques encompass semi‑structured interviews, field notes, and document analysis. Thematic analysis is applied to identify adaptation patterns among HR personnel, while source and technique triangulation ensure the validity of findings. Findings indicate that establishing a learning community at SD Negeri 01 Rejosari effectively enhances teachers’ capacity through collaboration, sharing of best practices, and mastery of instructional technologies. The study’s implications underscore the necessity of integrating learning community activities into professional development programs, providing ongoing expert mentoring, and employing case‑based learning methods to strengthen educators’ preparedness for evolving education policies.